STUDENT'S RECEPTION TOWARD SHAKESPEARE’S SELECTED CONTEMPORARY PLAYS - Dahlan; Junaid, Syahruni; Ahmad Muzammil; Rauf, Masykur (UIN Alauddin Makassar, 2022)
Literary reception is a literary genre that examines literary texts by considering the reader as the giver of the welcome or response. Researchers choose to analyze literary receptions in Shakespeare's plays, namely